TEKNOLOGI PENERANGAN JALAN UMUM (PJU) LED SMART SYSTEM TENAGA SURYA UNTUK MENDUKUNG OBJEK WISATA - Muh Akbar; Adik Putra Andika (Musamus Devotion Journal, 2022)
The limited village budget has prevented the development of Public Street Lighting (PJU) in Yasa Mulya Village. This clearly makes the business time of each trader not optimal because they can only trade from morning to evening. In 2020 the tourism sector was the sector that was most depressed due to the Covid 19 pandemic. Around 80% of small and medium enterprises from the tourism sector with millions of livelihoods around the world were affected by Covid-19. The purpose of this service is to improve the economy of Yasa Mulya Village by providing lighting at night using the PJU LED smart system technology. The method used in making this PJU LED smart system is a manufacturing system, namely by assembling PJU poles, solar cell frames, and electrical installations. From the results of design and testing, the dissemination of LED smart solar power system lighting technology is technically feasible to install because the power obtained from the solar cell is higher than the load power of the LED lamps used. In addition, with the installation of LED PJUs, the economy of Yasa Mulya Village will increase again and traffic safety at the Tugu Monument L.B. intersection. Moerdani becomes safer